A baropodometria como método de avaliação da distribuição da pressão plantar e estabilometria em portadores de doença de Parkinson - Gimenez, Francieli Vanessa (2019)
Introduction: Considered as a movement disorder, Parkinson's disease (PD) is a progressive and degenerative neurological disorder that predisposes to irreversible damage to the central nervous system due to the failure of dopaminergic neurons, leading to disabling motor dysfunction. Motor impairment shows balance and slowness of walking as a striking feature. In this sense, baropodometry is a reliable examination technique used to diagnose static and dynamic body oscillations, as well as the pressures exerted by the foot. Objective: To investigate of disorders of plantar pressure distribution and body sway of PD patients compared to healthy subjects through baropodometry and stabilometry. Methods: We evaluated 200 participants divided into 100 patients with PD between disease stages (Hoehn and Yahr Modified 1.5 to 3.0) and 100 healthy. Participants were evaluated for plantar pressures in static posture with eyes open and closed to determine the point of greatest pressure and stabilometry to assess displacements in the anteroposterior (AP) and mid-lateral axis (ML), as well as the distance from the center of pressure (CoP) and body displacement velocity and, dynamic posture to define the time of foot contact during gait. Results: There were no significant differences in the body sway variables in the AP and ML axis. There was a statistical difference in CoP displacement and body sway velocity between groups and between stage 1.5 and 3.0 considering p <0.05. Higher plantar pressure was observed in phase 3 of the step in the forefoot region in the PD group and statistical difference in contact time, in which the PD group remained longer in contact with the ground. Conclusion: Participants with PD had greater CoP distances and higher body sway velocity, higher forefoot pressure and longer ground contact time during walking than healthy individuals in the same age group. These instabilities were more evident as the disease progressed. Early interventions to alleviate the symptoms of the disease are recommended.